Analisis SWOT Dalam Strategi Pemasaran Pada Mcdonald’s - Juwairiazizah Rasta; Tia Deja Pohan; Nurbaiti Nurbaiti (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
Technological developments in Indonesia have an influence on current developments, especially fast food restaurants which are currently a trend among consumers, including McDonald's. With the trend of fast food such as McDonald's, many competitors have emerged with similar companies. This research was conducted with the aim of knowing and analyzing McDoanald's marketing strategy using a SWOT analysis consisting of Strengths, Weaknesses, Opportunities and Threats. The method in this research is a case study using SWOT analysis. The data used in this research is secondary data. On the other hand, qualitative research is a type of research that uses techniques to extract information using data sets that are larger than one point of view, such as journals, articles, and so on. This type of qualitative research is carried out by collecting clear data to analyze information related to ongoing research. The research results show that McDonald's has strengths, weaknesses, opportunities and threats in its marketing activities. The results of the analysis show that McDonald's must use a strategy to increase the effectiveness of promotions through advertising, media and existing websites as well as adding sponsorship and collaboration with other top artists.